35 Carer-administration of as-needed sub-cutaneous medication for breakthrough symptoms in homebased dying patients: a uk study (CARIAD). Issue 3 (1st September 2017) - Wilkinson, Clare; Poolman, Marlise; Roberts, Jessica; Wee, Bee; Hiscock, Julia; Hughes, Dyfrig; Nelson, Annmarie; Perkins, Paul; Johnstone, Rosalynde; Reymond, Liz; Foster, Betty; O'Connor, Julie; et al.
Abstract : Introduction: Whilst the majority of seriously ill people express a wish to die at home (79%), only half of those achieve this. The likelihood of patients remaining at home often depends on availability of able and willing informal carers who take on numerous care tasks, often including the responsibility of assisting patients with oral medications. The role of carers administering subcutaneous injections is not widespread practice in the UK, but has proven to be key in achieving home death in other countries. Aim: To determine if carer-administration of as-needed subcutaneous medication for four breakthrough symptoms (pain, nausea, restlessness and noisy breathing) in homebased dying patients is feasible and acceptable in the UK. Methods: One hundred adult patients in the last weeks of life who are likely to lose the oral route and have expressed a preference to die at home will be recruited with their carers to an external randomised pilot trial across three UK sites (North Wales, South Wales and Gloucestershire). Carers randomised to the intervention arm will receive a manualised training package adapted from an existing Australian model and delivered by local district nursing teams. Dyads in the control arm will receive usual care. Results: The main outcomes of interest will be feasibility, acceptability, recruitment rates, attrition and selection of the most appropriate outcomes measures. Conclusion: Findings will inform a definitive Phase III randomised controlled trial. The study is funded by the National Institute for Health Research (HTA project 15/10/37). The views expressed are those of the author(s) and not necessarily those of the NHS, the NIHR or the Department of Health.